Stock exchange governance initiatives: Evidence from the Italian STARs - Gleason, Kimberly C.; Madura, Jeff; Subrahmanyam, Vijaya (Journal of Banking & Finance, 2007)
Can a stock exchange improve corporate governance and transparency by designating companies that exhibit superior corporate governance? In 2000, the Borsa Italiana created a mid-cap segment with strong listing standards, which is composed of firms (called STARS) that follow stricter standards of transparency, disclosure, monitoring and liquidity. We find that STAR firms exhibit governance characteristics not observed in non-STAR firms, such as a higher incidence of audit and executive committees and higher debt ratios. They experienced a modestly favorable share price response upon the implementation of the STAR initiative. Moreover, they experienced significantly higher buy and hold returns and transparency after the initiative. Several governance characteristics are cross-sectionally associated with performance following the STAR initiative. Overall, the results suggest that firms may be willing to improve governance when they are endorsed by a credible agency for doing so, and such improvements may lead to better performance. The STAR initiative may serve as a model that can be adapted by other stock exchanges to promote transparency and governance.